Caridean prawn (Crustacea, Decapoda) with description of a new species and an invasive crayfish from Yuelu mountain national park, Hunan, China - Chen, Wen-Jian; Chen, Qing-Hua; Guo, Zhao-Liang (Zootaxa, 2018)
Yuelu mountain national park (5A scenic area) is a rare urban mountain scenic area. The major impacts from human activity are growing, such as largely unplanned tourist activity, urbanization, and accelerated the others responsible for environmental changes. It is unavoidable to have great pressure and influence on the diversity of fauna on the scenic area. In order to better understand the diversity of the decapod fauna in the Yuelu mountain national park, an intensive field survey has been carried out. A total of five species was collected, three species of atyid shrimps, Neocaridina palmata (Shen, 1948), N. yueluensis, new species, and Paracaridina longispina (Guo & He, 1992), one species of palaemonid prawn, Macrobrachium nipponense (De Haan,1849), and an invasive crayfish, Procambarus clarkii (Girard, 1852). N. yueluensis is distiguished from congeners by the shorter rostrum, the stout carpus of first pereiopod and the stout chela of second pereiopod, not sexual dimorphism of the third and fourth pereiopods, the long appendix interna and arising from the inner border of appendix masculina, and the narrower scaphocerite.